2020
DOI: 10.1017/fms.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for twisted symmetric square L-functions via half-integral weight periods

Abstract: We establish the first moment bound $$\begin{align*}\sum_{\varphi} L(\varphi \otimes \varphi \otimes \Psi, \tfrac{1}{2}) \ll_\varepsilon p^{5/4+\varepsilon} \end{align*}$$ for triple product L-functions, where $\Psi $ is a fixed Hecke–Maass form on $\operatorname {\mathrm {SL}}_2(\mathbb {Z})$ and $\varphi $ runs over the Hecke–Maass newforms on $\Gamma _0(p)$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is plausible that the methods used to prove Theorem 1.3 should also generalize to show formula (1.8) for Δ ≥ T 1/5+ , which would improve on [16], but this requires a rigorous proof. For quantum variance in the level aspect, see [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is plausible that the methods used to prove Theorem 1.3 should also generalize to show formula (1.8) for Δ ≥ T 1/5+ , which would improve on [16], but this requires a rigorous proof. For quantum variance in the level aspect, see [28].…”
Section: Resultsmentioning
confidence: 99%
“…(Lam’s work actually involves symmetric-square L -functions attached to holomorphic Hecke eigenforms, but his method should apply equally well to Hecke–Maass forms.) Other works involving moments of symmetric square L -functions include [3, 18, 16, 19, 2, 1, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Blomer et al [BHMM22] have demonstrated that one may use Voronoï summation for Rankin–Selberg convolutions in place of a theta kernel. Prior to the application to fourth moments, theta kernels have played similar roles in the study of quantum variance [Nel16, Nel17, Nel19, Nel20], numerical computations [Nel15] and in the proof of Waldspurger’s formula [Wal85]. In each of these earlier works, theta kernels apparently served as a substitute for parabolic Fourier expansions, giving a tool for establishing analogues on compact quotients (where such expansions are not available) of results known already for noncompact quotients.…”
Section: Introductionmentioning
confidence: 99%